2021
DOI: 10.1038/s41598-020-78867-1
|View full text |Cite
|
Sign up to set email alerts
|

1H-NMR metabolomics reveals a multitarget action of Crithmum maritimum ethyl acetate extract in inhibiting hepatocellular carcinoma cell growth

Abstract: Hepatocellular carcinoma (HCC) is nowadays the sixth cause of tumour-related deceases worldwide, estimated to become the third in Western countries by 2030. New drugs for HCC treatment still have many adverse effects. Several lines of evidence indicate that plant metabolites offer concrete opportunities for developing new therapeutic strategies for many diseases, including cancer. We previously reported that ethyl acetate extract of a spontaneous edible plant harvested in Apulia, Crithmum maritimum, significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 69 publications
(96 reference statements)
0
19
0
Order By: Relevance
“…The main constituents of sea fennel identified in this study were epigallocatechin, vanillic acid and chlorogenic acid [109]. The extracts from sea fennel plants exhibited notable anticancer properties [110]. In particular, Gnocchi et al [111] reported that the ethyl acetate extracts from sea fennel plants collected on the Apulian coast, Italy at a concentration of 0.5 µM showed anticancer activity against hepatocellular carcinoma cell lines (Huh7 and HepG2) by causing cell necrosis and apoptosis on the one hand and by reducing cancel cell growth on the other hand.…”
Section: Health Effectsmentioning
confidence: 67%
“…The main constituents of sea fennel identified in this study were epigallocatechin, vanillic acid and chlorogenic acid [109]. The extracts from sea fennel plants exhibited notable anticancer properties [110]. In particular, Gnocchi et al [111] reported that the ethyl acetate extracts from sea fennel plants collected on the Apulian coast, Italy at a concentration of 0.5 µM showed anticancer activity against hepatocellular carcinoma cell lines (Huh7 and HepG2) by causing cell necrosis and apoptosis on the one hand and by reducing cancel cell growth on the other hand.…”
Section: Health Effectsmentioning
confidence: 67%
“…It is worth noting that mass spectrometry can’t detect all the metabolites, not because the mass spectrometry is not sensitive enough, but because mass spectrometry can only detect ionized substances, but some metabolites can’t be ionized in the mass spectrometer. Nuclear magnetic resonance (NMR) is needed to make up for the lack of chromatography in the future, and further research is needed 36 38 . Through the metabonomic and natural product research combined, the content of ergosterol peroxide and (22E)-ergosta-4,6,8(14),22-tetraen-3-one showed a linear trend increase, which indicated the feasibility of their use as an indicator for fruiting body maturation, but whether this indicator can be applied for the commercial production of mushroom I. hispidus requires the verification of large-scale fruiting experiences.…”
Section: Discussionmentioning
confidence: 99%
“…At the time of collection, the cells were washed twice with ice cold PBS and lysed in ice-cold PBS by sonication. After removing the insoluble particles by centrifugation, the supernatants were immediately frozen at À80 C. Both cell lysates and culture media (500 mL samples) were added to 100 mL D 2 O buffer (0.1 M K 2 HPO 4 , 0.5 mmol/L DSS and 2 mmol/L sodium azide, pH 7.4) and transferred in 5-mm outer diameter NMR tubes (14,15,16). bacterial Fo F1-ATP synthase sandwiched by cyan fluorescent protein (CFP) and yellow fluorescent protein (YFP) variants.…”
Section: Nmr Measurementsmentioning
confidence: 99%